Awareness and use of nonoccupational post‐exposure prophylaxis among men who have sex with men in Vancouver, Canada. Issue 9 (1st August 2016) - Lin, SY; Lachowsky, NJ; Hull, M; Rich, A; Cui, Z; Sereda, P; Jollimore, J; Stephenson, K; Thumath, M; Montaner, JSG; Roth, EA; Hogg, RS; et al.
Abstract : Objectives: Nonoccupational post‐exposure prophylaxis (nPEP) is a strategy to reduce the risk of HIV infection in those with high‐risk exposure. This study characterized nPEP awareness among gay, bisexual and other men who have sex with men (MSM) in Metro Vancouver, British Columbia, Canada after a pilot nPEP programme established in 2012. Methods: Momentum Health Study participants were MSM aged ≥16 years recruited via respondent‐driven sampling (RDS) who completed a computer‐assisted self‐interview. Stratifying patients by HIV status, we used multivariable logistic regression with backward selection to identify factors associated with nPEP awareness. All analyses were RDS‐adjusted. Results: A total of 51.9% (112 of 173) of HIV‐positive and 48.5% (272 of 500) of HIV‐negative participants had heard of nPEP. Only 3% (five of 106) of HIV‐negative participants who reported recent high‐risk sex used nPEP. Generally, nPEP awareness was higher for participants who engaged in sexual activities with increased HIV transmission potential. Factors associated with greater awareness among HIV‐negative participants included recent alcohol use, higher communal sexual altruism, previous sexually transmitted infection diagnosis, and greater perceived condom use self‐efficacy. Other factors associated with greater awareness among HIV‐negative participants included white race/ethnicity, gay sexual identity, more formal education, lower personal sexual altruism, and Vancouver residence. Greater nPEP awareness among HIV‐positive participants was associated with greater perceived agency to ask sexual partners' HIV status and more frequently reporting doing so, a higher number of lifetime receptive sex partners, and greater access to condoms. Conclusions: Following implementation of an nPEP pilot programme, nPEP awareness among HIV‐negative MSM was 51% and use was 3%. These data support the need to expand access to and actively promote nPEP services.